2004
DOI: 10.1021/bi035938u
|View full text |Cite
|
Sign up to set email alerts
|

The Raised Midpoint Potential of the [2Fe2S] Cluster of Cytochromebc1Is Mediated by Both the QoSite Occupants and the Head Domain Position of the Fe−S Protein Subunit

Abstract: We have previously reported that mutant strains of Rhodobacter capsulatus that have alanine insertions (+nAla mutants) in the hinge region of the iron sulfur (Fe-S) containing subunit of the bc(1) complex have increased redox midpoint potentials (E(m)) for their [2Fe2S] clusters. The alteration of the E(m) in these strains, which contain mutations far from the metal binding site, implied that the local environment of the metal center is indirectly altered by a change in the interaction of this subunit with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 42 publications
5
55
0
Order By: Relevance
“…Addition of antimycin A to ordered membrane samples alters the EPR spectral shape of the [2Fe-2S] cluster of the cyt bc 1 In contrast to what was observed with the cyt b H and b L hemes, addition of either antimycin A or HQNO to membranes exhibited no discernable effect on the EPR transitions of the [2Fe-2S] cluster in non-ordered (or powder) sample EPR spectra ( Figures 3 and 4), as has been described earlier (26). Unlike the tensor averaged powder sample EPR spectra, use of ordered membrane samples increases both the spectral resolution of a given transition in the EPR spectrum, and also yields specific information about the relative orientation (and the relative numbers of different orientations) of a metal cluster in a given sample.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Addition of antimycin A to ordered membrane samples alters the EPR spectral shape of the [2Fe-2S] cluster of the cyt bc 1 In contrast to what was observed with the cyt b H and b L hemes, addition of either antimycin A or HQNO to membranes exhibited no discernable effect on the EPR transitions of the [2Fe-2S] cluster in non-ordered (or powder) sample EPR spectra ( Figures 3 and 4), as has been described earlier (26). Unlike the tensor averaged powder sample EPR spectra, use of ordered membrane samples increases both the spectral resolution of a given transition in the EPR spectrum, and also yields specific information about the relative orientation (and the relative numbers of different orientations) of a metal cluster in a given sample.…”
Section: Resultssupporting
confidence: 69%
“…In these cases, the total amount of the Fe/S protein residing at the cyt b surface was diminished, and the EPR g y transition of the [2Fe-2S] cluster shifted to slightly lower magnetic field positions. Furthermore, in similarly ordered membranes increased mobility of the Fe/S protein was also accompanied by a diminished orientation dependence of the [2Fe-2S] cluster spectrum (26). The similarities of these observations to the data obtained by addition of antimycin A suggested that the membrane embedded cyt bc 1 has an increased mobility of the Fe/S protein subunit.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The same crystal form has been obtained without stigmatellin, however the resolution (7 Å) was not high enough to describe the occupation of the Qo site. Efforts are currently under way to crystallize one of the "neck" mutants (Darrouzet et al 2000;Cooley et al 2004), which seem to hold the ISP prefferentially in a position similar to the stigmatellin position, in the absence of stigmatellin.…”
Section: Rb Capsulatus Cyt Bc 1 Versus Its Mitochondrial and Chloropmentioning
confidence: 99%